Fabrication and characterisation of high sensitivity copper‐copper oxide‐copper (Cu‐CuO‐Cu) metal‐insulator‐metal tunnel junctions. Issue 5 (1st February 2013) - Abdel‐Rahman, M.; Syaryadhi, M.; Debbar, N.
Abstract : A report is presented on the realisation and characterisation of symmetrical metal‐insulator‐metal (MIM) diodes using the new material combination: copper‐copper oxide‐copper (Cu‐CuO‐Cu). The MIM diodes, having contact areas of 2 × 2 µm 2, were fabricated using electron beam lithography and sputter deposition. The MIM diodes exhibited an absolute sensitivity as high as 4.497 V − 1 .